IMPACT ANALYSIS OF KEY PERFORMANCE INDICATORS OF THE BROADBAND ACCESS MARKET IN RUSSIA ON COST OF THE TELECOMMUNICATIONS COMPANIES - V. I. Busov; T. F. Khan’ (Вестник университета)
Based on the analysis of the Russian broadband access market, the main drivers of growth in the cost of telecommunications companies in this business sector; its main trends – the preservation of high dividend yield of companies in the Russian broadband market, stable and moderate growth of the customer base, a large debt burden, the presence of significant investment projects have been determined. The influence of capital costs and charges on capitalization of telecommunications companies in the broadband sector of the national market and companies with the greatest growth prospects have been identified.